Early Maternal Time Investment and Early Child Outcomes - Emilia Del Bono; Marco Francesconi; Yvonne Kelly; Amanda Sacker (Institute for the Study of Labor (IZA), 2014)
Using large longitudinal survey data from the UK Millennium Cohort Study, this paper estimates the effect of maternal time inputs on early child development. We find that maternal time is a quantitatively important determinant of skill formation and that its effect declines with child age. There is evidence of a long shadow of the effect of early maternal time inputs on later outcomes, especially in the case of cognitive skill development. In the case of non-cognitive development, this effect disappears when we account for skill persistence.
Keywords: J24; J15; I20; 330; education production functions; early interventions; cognitive and non-cognitive skill formation